Molecular weight characterization of single globular proteins using optical nanotweezers. Issue 14 (5th March 2015) - Wheaton, Skyler; Gordon, Reuven
Abstract : We trap a set of molecular weight standard globular proteins using a double nanohole optical trap. Abstract : We trap a set of molecular weight standard globular proteins using a double nanohole optical trap. The root mean squared variation of the trapping laser transmission intensity gives a linear dependence with the molecular weight, showing the potential for analysis of globular proteins. The characteristic time of the autocorrelation of the trapping laser intensity variations scales with a −2/3 power dependence with the volume of the particle. A hydrodynamic laser tweezer model is used to explain these dependencies. Since this is a single particle technique that operates in solution and can be used to isolate an individual particle, we believe that it provides an interesting alternative to existing analysis methods and shows promise to expand the capabilities of protein related studies to the single particle level.